Identification of age-specific gene regulators of La Crosse virus neuroinvasion and pathogenesis - Rahul Basu; Sundar Ganesan; Clayton W. Winkler; Sarah L. Anzick; Craig Martens; Karin E. Peterson; Iain D. C. Fraser (Nature Communications, 2023)
Abstract One of the key events in viral encephalitis is the ability of virus to enter the central nervous system (CNS). Several encephalitic viruses, including La Crosse Virus (LACV), primarily induce encephalitis in children, but not adults. This phenomenon is also observed in LACV mouse models, where the virus gains access to the CNS of weanling animals through vascular leakage of brain microvessels, likely through brain capillary endothelial cells (BCECs). To examine age and region-specific regulatory factors of vascular leakage, we used genome-wide transcriptomics and targeted siRNA screening to identify genes whose suppression affected viral pathogenesis in BCECs. Further analysis of two of these gene products, Connexin43 (Cx43/Gja1) and EphrinA2 (Efna2), showed a substantial effect on LACV pathogenesis. Induction of Cx43 by 4-phenylbutyric acid (4-PBA) inhibited neurological disease in weanling mice, while Efna2 deficiency increased disease in adult mice. Thus, we show that Efna2 and Cx43 expressed by BCECs are key mediators of LACV-induced neuroinvasion and neurological disease.